TVT for the treatment of urodynamic stress incontinence: Efficacy and adverse effects at 13‐year follow‐up. Issue 1 (19th October 2015) - Serati, Maurizio; Sorice, Paola; Bogani, Giorgio; Braga, Andrea; Cantaluppi, Simona; Uccella, Stefano; Caccia, Giorgio; Salvatore, Stefano; Ghezzi, Fabio
Abstract : Aim: To assess long‐term subjective, objective, and urodynamic outcomes of retropubic mid‐urethral slings at 13‐year follow‐up. Methods: This was a prospective observational study. Consecutive women with proven urodynamic stress incontinence were treated with standard retropubic tension free vaginal tape (TVT). Patients with mixed incontinence and/or anatomic evidence of pelvic organ prolapse were excluded. All the included patients underwent preoperative clinical and urodynamic evaluations. During follow‐up examinations, women were assessed for subjective satisfaction and objective cure rates. The Cox model was used in order to investigate factors predicting the risk of recurrent stress urinary incontinence (SUI), over the study period. Results: Overall, 55 patients were suitable for the analysis. At 13‐year follow‐up, 47 out of 55 (85.5%) patients declared themselves cured (p‐for‐trend 0.02) and 48 out of 58 (87.2%) were at least improved (p‐for‐trend 0.07). No significant deterioration of objective cure rates was observed over time ( P  = 0.29). At the time of the last evaluation, 50 out of 55 (90.9%) women were objectively cured; urodynamic evaluation confirmed this finding in 49 (89.1%) patients. Considering factors predictive of SUI recurrence, we observed that, via multivariate analysis, obesity (HR 7.2; P  = 0.01) and maximum detrusor pressure during the voiding phase ≤29 cmH2 O (HR 8.0; P  = 0.01) were the only independent predictors of recurrent SUI. Conclusion: Our data confirmed that TVT is a highly effective and safe procedure also at 13‐year follow‐up. Interestingly, we observed a significant decrease of subjective satisfaction over time. Neurourol. Urodynam. 36:192–197, 2017 . © 2015 Wiley Periodicals, Inc.